Assessing the Needs and Limitations of Health Information Systems in Sudan - Mohamed Omer Mohamed; Mudawi Mukhtar Elmusharaf; Abubaker Abdellbagi Adam; Ahmed Abdelrahman Mohamed (المجلة الدولية للحاسبات والمعلوماتية, 2025)
The health information system is an essential part of the health system. Having a comprehensive and flexible health information system is extremely important. It improves the quality of health care and helps in managing the health system with high efficiency with planning and follow-up planning. To achieve this, it is necessary to understand the current health information system, identify the challenges it faces, and evaluate the needs. A qualitative methodology was followed, where semi-structured interviews were conducted with a number of stakeholders and participants in the health services in its various fields. The data collected from the interviews were analyzed. The result of this analysis reveals a good understanding of the current status of the health information system, an understanding of the status of the health system before and after the war, and identifying the current problems and obstacles. The study found gaps in the current health information system, including that there are many sources of information outside the health information system, and even the information collected is usually estimated and inaccurate. There is no unified mechanism for exchanging information between different health institutions. There is only one approved system for collecting health information, which is DHIS2. The study concludes with the necessity of introducing information sources that operate outside the umbrella of health information systems, with the integration of health information sources, with the need to create a framework through which health information is unified and exchanged.